Airway Sensory Nerve Plasticity in Asthma and Chronic Cough - Drake, Matthew G.; Cook, Madeline; Fryer, Allison D.; Jacoby, David B.; Scott, Gregory D. (Frontiers in Physiology, 2021)
Airway sensory nerves detect a wide variety of chemical and mechanical stimuli, and relay signals to circuits within the brainstem that regulate breathing, cough, and bronchoconstriction. Recent advances in histological methods, single cell PCR analysis and transgenic mouse models have illuminated a remarkable degree of sensory nerve heterogeneity and have enabled an unprecedented ability to test the functional role of specific neuronal populations in healthy and diseased lungs. This review focuses on how neuronal plasticity contributes to development of two of the most common airway diseases, asthma and chronic cough, and discusses the therapeutic implications of emerging treatments that target airway sensory nerves.